Assessing the Patient Falls in Hospitals Affiliated to Tehran University of Medical Sciences - M Shali; S Joolaee; KH Vaskooi; N Bahrani (Iran University of Medical Sciences, 2016)
Abstract Background & Aims: Falling is one of the most common events that threats physical and psychological safety in patients, as well a factor that increases duration of hospitalization and treatment costs. The aim of the study was to investigate patient fallings kinds, characteristics and related factors to reduce risk factors in patients admitted to hospitals affiliated to Tehran University of Medical Sciences. Material & Methods: In this descriptive study, 285 patients' records were selected by cluster sampling method. Data were collected through a standard form including demographic and patient fall characteristics. Then data were analyzed by using SPSS software (v.16), chi-square test, and frequency tables. Results: Our results showed that the majority of fallen patients were male with a mean age of 60 years, also the most of cases had bed falling (58.6%) in night (4Am-7Pm). In 35.8% of falling cases, there were no witness and 75.8% of patients were not able to rise after falling. Scratches, head injury, soft tissue injuries and fractures were the reported complications of the patients falling. Conclusion: Given the high rate of falling patients' incidence, it is essential to offer effective management strategies to provide more safety situation for patients.